THE CONSEPT AND ITS IMPLEMENTATION OF INDONESIAN LEGISLATIVE ELECTIONS BASED ON THE PANCASILA DEMOCRACY PERSPECTIVE - Wartoyo, Franciscus Xaverius; Tungga, Benyamin (Yustisia, 2019)
Indonesia’s democracy system was built on the basis and the strength of Pancasila, which did not favor the excessive desires of individual negotiations (liberalism) neither absolute state domination, non-liberalism, namely direct and indirect democracy that was once practiced. Those forms have their own weaknesses, but this paper will only highlight the positive side of the open democratic system, sincerely the democratic system of this nation is Pancasila democracy which refers to those two major forces of democracy. The implementation of Pancasila’s democracy in the Legislative Election can be shown in Law Number 7 of 2017 on the General Elections 2019 in Indonesia. The history of the implementation of elections in Indonesia revealed a variety of dynamics indicated by several changes in the constitutional law which were used as the basis for the implementation of elections. The publication of the Election Law is the elaboration of the provisions of Article 22E of the 1945 Indonesian Constitution. This means that the principles of democracy contained within 1945 Constitution of the Republic of Indonesia, must become the main foundations in designing norms in Law Number 7 of 2017 on the General Elections 2019, as happened, it turns out that the parliamentary threshold regulation within the Constitutional Law are ineffective in implementing this democracy.